2015
DOI: 10.1002/mnfr.201570094
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipids modulate the expression of miR‐107, a miRNA that regulates the circadian system

Abstract: Scope:The increased prevalence of cardiovascular diseases (CVDs) has been hypothesized to be the result of an increased exposure to a host of atherogenic environmental factors, paramount among them being unhealthy dietary habits. Long-chain n-3 polyunsaturated fatty acids (PUFAs) have been shown to have cardio protective effects, partially due to their ability to regulate gene expression. In this regard, increasing attention has been devoted to the role of miRNAs as regulators of multiple metabolic pathways wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Overexpression of miR‐93 has been reported to be useful in treating coronary atherosclerosis (He et al, ). More important, a previous study had revealed that miR‐107 was expected to be a novel therapeutic direction for various diseases including atherosclerosis (Daimiel‐Ruiz et al, ). On the basis of those findings, our results verified the hypothesis that miR‐107 may be an antiatherosclerosis miRNA as well.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR‐93 has been reported to be useful in treating coronary atherosclerosis (He et al, ). More important, a previous study had revealed that miR‐107 was expected to be a novel therapeutic direction for various diseases including atherosclerosis (Daimiel‐Ruiz et al, ). On the basis of those findings, our results verified the hypothesis that miR‐107 may be an antiatherosclerosis miRNA as well.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, metabolism of dietary lipids by gut microbiota results in production of energy as well as signaling molecules that influence multiple pathways . Just recently it was shown that in vitro treatment of Caco‐2 cells with dietary lipids such as cholesterol, docosahexanoic acid, and conjugated linoleic acid resulted in 29 differentially regulated miRNAs . Among these, miR‐107, previously implicated in the regulation of metabolic diseases and cancer , was significantly up‐regulated by all these three lipids.…”
Section: Gut Microbiota and Mirnas: Do Gut Microbes Regulate Host Mirmentioning
confidence: 99%
“…Among these, miR‐107, previously implicated in the regulation of metabolic diseases and cancer , was significantly up‐regulated by all these three lipids. Although the molecular mechanism through which miRNA‐107 impacts metabolic pathways is not fully understood, it was suggested that this could be through modulation of the circadian system . It was also reported that gut microbiota down‐regulates miRNA‐107 in myeloid cells and in macrophages .…”
Section: Gut Microbiota and Mirnas: Do Gut Microbes Regulate Host Mirmentioning
confidence: 99%
“…In particular, cell‐based studies have implicated miR‐192, miR‐194 and miR‐29 in the regulation of the human Per gene family (Nagel, Clijsters, & Agami, ) and miR‐24, miR‐29a and miR‐30a in the regulation of the mouse Per gene family (Chen, D'Alessandro, & Lee, ; Zhao et al, ) (see Figure ). In humans, miR‐107 controls the circadian rhythm of cells by binding to the Clock gene (Daimiel‐Ruiz et al, ). In mice, miR‐494, miR‐142‐3p and miR‐27b‐3p may function as post‐transcriptional modulators of Bmal1 , but only miR‐494 follows a circadian expression pattern (Shende, Goldrick, Ramani, & Earnest, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%